POST FEVER RETINITIS AND SINGLE WONDER DRUG FOR ITS VARIOUS ETIOLOGIES - Sharma, Vikas; K, Raji; Seth, Sankalp; Yadav, Yogesh; Kapoor, Gaurav (International Journal of Retina, 2023)
Introduction: Post-fever retinitis is an infectious or para-infectious entity which involve retinal layer of the eye and has variable clinical manifestations. Post-fever retinitis has varied etiologies, namely bacteria or viral. Case Report: We present a series of four cases of post fever retinitis with common history of flu-like illness followed by blurring of vision, all four patients had different clinical picture, they were investigated thoroughly to ascertain etiological agents and were treated with oral Doxycycline. All cases had an excellent visual recovery by the end of the treatment with complete resolution of clinical signs. Discussion: It is difficult to pin-point the exact etiology of PFR just on the basis of clinical presentation and hence, proper history, clinical examination, serological investigations and awareness of ongoing epidemics may help to identify the etiological organism. Conclusion: Post fever retinitis is an easy diagnosis based on antecedent history of flu like illness and typical fundus findings. Oral doxycycline is a safe and wonderful drug for PFR cases.